Comparison of the incidence of high-grade squamous intraepithelial lesions (HSIL) between women infected with HPV 16/18 and Non-16/18 types - Jomjak, Phiset (Journal of Nakornping Hospital, 2025)
Background: Human papillomavirus (HPV) infection, particularly with types 16 and 18, is a major risk factor for the development of high-grade squamous intraepithelial lesions (HSIL) of the cervix. However, other high-risk HPV types (non-16/18) may also lead to HSIL, especially in cases of persistent infection. Evidence regarding the incidence of HSIL and associated risk factors in the Thai context remains limited. Therefore, further studies are warranted to provide empirical data to support appropriate prevention, screening, and management strategies. Objectives: To compare the incidence of HSIL between women infected with HPV types 16/18 and non-16/18, and to analyze the risk factors associated with its progression. Methods: A cross-sectional descriptive study was conducted using retrospective data from women infected with high-risk HPV who underwent colposcopy at Sanpatong Hospital, Chiang Mai Province, between 2014 and 2024. A total of 599 cases were included. Data were analyzed using descriptive statistics, the Chi-square test or Fisher’s Exact test, and Binary Logistic Regression. Results: The participants had a mean age of 47.45 ± 9.68 years, with 40.57% aged between 50 and 59 years. The incidence of HSIL was 47.69% in the HPV 16/18 group and 39.94% in the non-16/18 group (p = 0.056). Factors significantly associated with HSIL were non-use of oral contraceptive pills (AOR = 0.27, 95% CI = 0.18–0.38, p < 0.001), husband’s smoking (AOR = 6.00, 95% CI = 3.67–9.81, p < 0.001), and HIV infection (AOR = 2.62, 95% CI = 1.35–5.10, p = 0.005). The predictive model demonstrated a classification accuracy of 66.10% and an area under the ROC curve (AuROC) of 0.72, indicating fair to good discrimination. Conclusion: Oral contraceptive use, husband’s smoking, and HIV infection were significantly associated with HSIL. Although HPV non-16/18 infection was not statistically significant, it was still associated with a considerable rate of HSIL, underscoring the importance of vigilant monitoring.